Temperature, flow and eccentricity measurements in a journal bearing with a single axial groove at 90º to the load line - Costa, Lucrécio (2000)
Parametric experiments have been conducted to analyse the influence of some supply conditions on the performance of a steadily loaded journal bearing. Temperature distribution on the internal surface, flowrate and bearing eccentricity were measured for different sets of operating conditions, at variable supply conditions. Quantitative information is provided which shows the effect of both shaft speed and applied load on maximum bush temperature and flowrate. It has been observed that flowrate was modestly affected by load and significantly affected by rotational speed, oil supply temperature and supply pressure. Maximum bush temperature was modestly affected by supply pressure, moderately affected by load and significantly affected by shaft speed. For low applied loads, the attitude angle was markedly affected by supply pressure. The experimental results also showed that for a small groove length there is a variation of bush temperature in axial direction in the groove region.